Polydatin attenuates renal fibrosis in diabetic mice through regulating the Cx32-Nox4 signaling pathway - Chen Zhi-quan; Sun Xiao-hong; Li Xue-juan; Xu Zhan-chi; Yang Yan; Lin Ze-yuan; Xiao Hai-ming; Zhang Meng; Quan Shi-jian; Huang He-qing (Acta Pharmacologica Sinica, 2020)
We previously found that polydatin could attenuate renal oxidative stress in diabetic mice and improve renal fibrosis. Recent evidence shows that NADPH oxidase 4 (Nox4)-derived reactive oxygen species (ROS) contribute to inflammatory and fibrotic processes in diabetic kidneys. In this study we investigated whether polydatin attenuated renal fibrosis by regulating Nox4 in vitro and in vivo. In high glucose-treated rat glomerular mesangial cells, polydatin significantly decreased the protein levels of Nox4 by promoting its K48-linked polyubiquitination, thus inhibited the production of ROS, and eventually decreasing the expression of fibronectin (FN) and intercellular adhesion molecule-1 (ICAM-1), the main factors that exacerbate diabetic renal fibrosis. Overexpression of Nox4 abolished the inhibitory effects of polydatin on FN and ICAM-1 expression. In addition, the expression of Connexin32 (Cx32) was significantly decreased, which was restored by polydatin treatment. Cx32 interacted with Nox4 and reduced its protein levels. Knockdown of Cx32 abolished the inhibitory effects of polydatin on the expression of FN and ICAM-1. In the kidneys of streptozocin-induced diabetic mice, administration of polydatin (100 mg·kg−1·d−1, ig, 6 days a week for 12 weeks) increased Cx32 expression and reduced Nox4 expression, decreased renal oxidative stress levels and the expression of fibrotic factors, eventually attenuating renal injury and fibrosis. In conclusion, polydatin promotes K48-linked polyubiquitination and degradation of Nox4 by restoring Cx32 expression, thereby decreasing renal oxidative stress levels and ultimately ameliorating the pathological progress of diabetic renal fibrosis. Thus, polydatin reduces renal oxidative stress levels and attenuates diabetic renal fibrosis through regulating the Cx32-Nox4 signaling pathway.